Propagation Of Almond Through Budding Under Temperate Conditions Of North Western Himalaya (Applied Biological Research, 2016)
An experiment was carried out in Fruit Plant Nursery of Division Fruit  Science, SKUAST-K, Shalimar, Kashmir during 2014 to standardize  budding method, time of budding for almond (Prunus dulcis) and to  determine the suitable portion of scion for maximum success. T-budding  with 51.2% success proved significantly superior over chip budding  (42.3%). Of the four budding timings tested, the highest budding success  of 52.1% was achieved when budding was done in 2nd week of June.  Overall, highest success of 49.4% was achieved when middle scion  portion was used for budding than the lower scion portion which gave  overall success of 44.1%. Of the varieties evaluated cultivar ‘Non-Pareil’  with budding success of 49.8% showed significant superiority over cv.  ‘Shalimar with budding success of 43.7%. Highest bud take (65.65%),  shoot length (25.9 cm) and shoot diameter (4.16 mm) were observed in  T-budding performed in the 2nd week of June. T-budding resulted in better success as compared to chip during June, July and August however chip budding performed significantly better in the month of September in both the cultivars.
Keywords: Almond; budding; scions; varieties